PENGGUNAAN MEDIA SOSIAL TERHADAP MOTIVASI BELAJAR SISWA KELAS VI DI SD NEGERI 1 LAMBHEU ACEH BESAR - Maulida Putri; Linda Vitoria; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the influence of social media usage on the learning motivation of sixth-grade students at SD Negeri 1 Lambheu, Aceh Besar Regency. This study was motivated by the high use of social media among elementary school students, which may influence their learning motivation. This research employed a quantitative approach with a correlational design. The population consisted of all sixth-grade students at SD Negeri 1 Lambheu, totaling 50 students, all of whom were used as the sample (total sampling). Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, a normality test, Pearson Product Moment correlation, simple linear regression, an F-test, and the coefficient of determination with the assistance of SPSS. The results showed a positive and significant influence of social media usage on students' learning motivation, evidenced by an F-count value of 11.398, greater than the F table value of 4.043, with a significance value of 0.001 < 0.05. The simple linear regression equation obtained was Y = 32.208 + 0.424X. The coefficient of determination (R²) of 0.192 indicated that social media usage contributed 19.2% to students' learning motivation, while the remaining 80.8% was influenced by other factors outside this study. It can therefore be concluded that social media usage has a positive and significant influence on the learning motivation of sixth-grade students at SD Negeri 1 Lambheu, Aceh Besar.